High-dose Somatostatin Analogues for Progressive Neuroendocrine Tumours - Sharp, Anna J (Eur Endocrinol, 2020)
Neuroendocrine tumours are a heterogeneous group of neoplasms with a variety of treatment options, but studies suggest they should in most cases, if they are not curable surgically, be treated initially with monthly long-acting somatostatin analogues. New data recently published suggest that if patients show progression on the current analogues at the recommended doses, increasing the dose or frequency of these analogues may provide a further therapeutic effect, although proper randomised trials will be necessary to confirm this effect.